Mourned Choices and Grievable Lives: The Anti‐Abortion Movement's Influence in Defining the Abortion Experience in Australia Since the 1960s. Issue 2 (12th July 2016) - Millar, Erica
Abstract : This article provides a genealogy of foetocentric grief, an emotion that permeates accounts of abortion in Australia across multiple discursive sites. Foetocentric grief represents women as indelibly mourning their 'unborn children' after abortion. The emotion first came to prominence in anti‐abortion activism of the mid‐1980s. Focus on the purported consequences of abortion for women enabled anti‐abortionists to respond to charges that they were unsympathetic towards women who have abortions. Foetocentric grief also transcribes the primary claim of the anti‐abortion movement – that abortion entails a mother's destruction of her unborn child – onto the very experience of abortion. Since the mid‐1980s, foetocentric grief has moved outside the anti‐abortion movement to dominate accounts of the abortion experience in the print media as well as, surprisingly, mainstream pro‐choice activism. This article maps the convergence of these trends and examines the political and regulatory effects of foetocentric grief. It argues that foetocentric grief is a culturally enforced emotion that discursively recuperates the figure of the aborting woman to normative regimes of pregnancy and femininity, where pregnant women are envisaged as already mothers to autonomous foetal‐subjects.